Use Digital Elevation Model In Extracting Drainage Network AndMeasurements Hydroformetric Of Al-Uthaim Basin - Jwad, Ali; Mohammed, Yousif (Iraqi Journal of Science, 2024)
This study aimed to build data base of the morphometric properties in theUdhaim basin , through analyzing the digital elevation model ( DEM ) by using amodel in a geographical information systems programs , which integrated togetherin order to obtain the morphometric variances & measurements. This is done tounderstand its hydrologic significances & consequently understanding the watermovement on the surface of the base. The study depended on the data of the digitalelevation model accurately 30 m while the results gave a good matching with theSatellite images. Moreover, the study shows that the form of the catchment's areas isclosed to the triangle while the main basin does not close to that shape, so that itcharacterized by systematic flow increased in the spring time .Also it is noticed thatthere is uniformity in the form of the catchments areas due to the similarity in thegeomorphic processes.